Education in transition - Borien, K; Borien, Keith Michael 1951 (2004)
﻿ The purpose of this research is to try to understand why educational restructuring since 1994 appears to have failed to achieve the government's stated objectives of development, equity, participation and redress for large sections of South African society. As the educational inequalities of the past appear to prevail beyond the arrival of the first democratic government, the hypothesis that little has fundamentally changed is explored. Although the study is firmly focussed on the period between 1994 and 1999, the legacy of the apartheid years is also examined to ensure that the research is firmly rooted in its historical context. The key area for analysis within a qualitative paradigm is the dynamic which exists between central government and its key role in planning educational reform and in policy formulation, and the provincial administrations, in whom the major responsibility for policy implementation and for effecting change on the ground, is vested. Local realities, dynamics, and constraints on the ground are explored in some depth in one of South Africa's nine provinces: the Eastern Cape. Access to the Eastern Cape's Department of Education and Culture was successfully negotiated in October 1997. As a consequence a total of 40 interviews were held with a mix of previous Ministers of Education and Culture, retired and serving Senior Civil Servants, ex members of two transitional provincial bodies, senior representatives of the main teacher unions and non-governmental organisations, school principals and school teachers. The data collected as part of this study was analysed using the grounded theory approach. The analysis indicates that educational change in the Eastern Cape will not come quickly, and that for many who were previously disadvantaged under the apartheid system little has fundamentally changed in the first five years of the new democratic South Africa.